Face validity of the LEAPA instrument for morphologic description of benign organic injury of the vocal folds (Research, Society and Development, 2020)
Objectives: The study aims to present the face and content validation of the LEAPA instrument, proposing a systematization for static description of the laryngoscopic findings of the benign organic lesions of the vocal folds with emphasis on the use of key elements of the morphological description (location / L / , extension / E /, organic aspect / A /, plurality / P /, associations / A /). The importance of this instrument is that dysphonia is highly prevalent world wide and in about 50% of cases it occurs due to benign vocal fold injuries. Thus, the morpho-functional visualization of the larynx through laryngoscopy and the ability to write a reliable technical report of the examination findings are essential for the correct diagnosis of dysphonia. Methods: A face evaluation was developed by 13 laryngology specialists to analyze the reliability of the lesion description method using Cronbach's alpha coefficient using 17 thought-provoking questions. Results: the LEAPA instrument obtained high internal consistency and high reliability (alpha 0.94). Conclusion: LEAPA allows the morphological description of benign vocal fold injuries, contributing to the preparation of concise laryngoscopic reports, with a uniform, reliable and correct diagnostic impression for this group of injuries.